Basic objects of marketing in project activities - Онищенко, Світлана Петрівна; Берневек, Тетяна Іванівна (Eastern-European Journal of Enterprise Technologies, 2013)
The article identified the main types of a project product from the point of view of a business level that is necessary to determine the specificity of the project marketing. As such objects of marketing - variants of the project product we have singled out: a product, a combination "product-market segment," a commodity group, a strategic business unit, a company. We have analyzed the relation "product life cycle - project-organization" and received a generalized representation of this relation. It was determined that the project product, generally speaking, may be smaller or longer than the duration of the project. It was determined that the project marketing in terms of objectives is wider than the marketing of goods, commodity group, strategic business unit and company. It was concluded that the specific project marketing objectives are distributed according to the stages of the project life cycle and related to the areas of knowledge of management of projects (to the greatest extent with the management of the content, timing, costs, risks) and should take into account the specificity of the current marketing activities of the enterprise, which implements the project